Implementation of a health communication strategy in the success of the COVID-19 vaccine program in West Jakarta - Afdal Makkuraga Putra; Awaliyah Rizka Safitri (Penerbit Universiti Kebangsaan Malaysia, 2024)
The research will focus on the West Jakarta Health Service's Communication Strategy for Disseminating the COVID-19 Vaccine. This research is inspired by the concern that the Jakarta COVID-19 vaccination achievement remains below target, particularly for the elderly, at 64.85 percent for the first dose and 58.44 percent for the second dose in October 2021. There are many obstacles such as hoax news and low public knowledge about vaccines. This research focuses on how to examine the Jakarta Health Office's communication strategy in inviting people to implement COVID-19 immunization. This research will expand on health communication concepts and theories by employing Push, Pull, and Pass communication tactics. A variety of doctors, and health professionals were interviewed for this study. The study results show that the push approach is implemented by opening direct vaccine centres, pulling through persuasively, door prizes, basic food packages, cooperation cross-sectors, and passes with public figure testimonials. The job of Dasawisma cadres is critical because they are the ones who directly persuade the people in simple languages like Javanese and Sundanese. The community also trusts the Dasawisma cadres because they are previously acquainted. The City of West Jakarta achieved 98% of the first dosage of the vaccination, and 65% dosage 2nd in December 2022.